2007
DOI: 10.1038/sj.eye.6702938
|View full text |Cite
|
Sign up to set email alerts
|

Immediate intraocular pressure changes following intravitreal injections of triamcinolone, pegaptanib, and bevacizumab

Abstract: Purpose To assess the intraocular pressure (IOP) changes, within the first 30 min after intravitreal injection of 0.1 ml (4 mg) triamcinolone, 0.09 ml (0.3 mg) pegaptanib, and 0.05 ml (1.25 mg) bevacizumab. Methods Records of patients who received intravitreal triamcinolone, pegaptanib, and bevacizumab and who had their IOP measured post-injection were reviewed. Results A total of 212 injections were performed (76 bevacizumab in 63 patients, 42 triamcinolone in 41 patients, 94 pegaptanib in 74 patients). At 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
3
22

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(140 citation statements)
references
References 4 publications
6
101
3
22
Order By: Relevance
“…29 Intraocular pressure elevation Acute rise of intraocular pressure (IOP) after intravitreal injection is injectionprocedure-related and lasts a few hours at most. 30,31 Recent studies, however, have reported a significant number of intravitreal anti-VEGF injections is associated with an increased risk for IOP elevation. 32,33 Patients with pre-existing glaucoma have higher rates of IOP elevation compared with those without pre-existing glaucoma.…”
Section: Methodsmentioning
confidence: 99%
“…29 Intraocular pressure elevation Acute rise of intraocular pressure (IOP) after intravitreal injection is injectionprocedure-related and lasts a few hours at most. 30,31 Recent studies, however, have reported a significant number of intravitreal anti-VEGF injections is associated with an increased risk for IOP elevation. 32,33 Patients with pre-existing glaucoma have higher rates of IOP elevation compared with those without pre-existing glaucoma.…”
Section: Methodsmentioning
confidence: 99%
“…Bakri et al 8 compared IOP elevation after intravitreal injection of 0.3 mg Pegaptanib, 4 mg Triamcinolone and 1.25 mg Bevacizumab. Review of patient records reported that approximately 87% of eyes administered each drug recorded an IOP of less than 35 mmHg 10 min after injection.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] It was our assessment that some of the previously used techniques used to assess the rise in IOP and anterior segment anatomy, in these reports, were not the ideal techniques that could have been used. We aimed to further clarify the effect of intravitreal injection of anti VEGF agents upon intraocular pressure (IOP) and anterior chamber structure using a previously validated technique of Ultrasound biomicroscopy (UBM).…”
Section: Introductionmentioning
confidence: 96%
“…Bu yan etkilerden biri de ani GİB artışıdır. Artmış vitreus volümüne bağlı olarak enjeksiyondan hemen sonra GİB artışı beklenen bir durum olup çeşitli çalışmalarda geçici veya kalıcı özellikte olabileceği bildirilmiştir [5][6][7][8][9]. Daha önceki çalışmalara benzer şekilde bizim çalışmamızda da enjeksiyondan hemen sonra GİB'de anlamlı bir artış olduğu ve 24. saatte bu artışın normal değerlerine geri döndüğü izlendi.…”
Section: Discussionunclassified
“…Enjeksiyon ile ilgili (uygulanan enjeksiyon volümü, ve enjeksiyon sonrası reflü) ve göz ile ilgili (aksiel uzunluk, skleral rijidite, vitreus yapısı) faktörlere bağlı olmak üzere neredeyse tüm intravitreal enjeksiyonlardan sonra ortaya çıkan bir yan etki de ani göziçi basıncı (GİB) artışıdır [5][6][7][8][9]. Enjeksiyon sonrası ani GİB artışı ve oküler aksiyel uzunluk (AU) değişikliği ile ilgili çok sayıda çalışma bulunmasına karşın lensin, glokom mevcudiyetinin ve daha önceden enjeksiyon uygulanmış olmanın bu değişiklikler üzerindeki etkisini ortaya koyan bir çalışma bulunmamaktadır [6,10,11].…”
Section: Introductionunclassified